Adult tinea capitis and tinea barbae in a tertiary Portuguese hospital: A 11‐year audit. Issue 11 (9th September 2019) - Duarte, Bruno; Galhardas, Célia; Cabete, Joana
Summary: Adult tinea capitis and tinea barbae are nowadays considered uncommon in developed countries. Despite their potential for morbidity and healthcare costs, few series have attempted to characterise these infectious disorders. We conducted a cross‐sectional study to analyse the epidemiological, clinical and mycological characteristics of adult tinea capitis and tinea barbae of a large tertiary centre in Southern Europe. All adult patients with a mycological‐confirmed tinea capitis or barbae over a 11‐year period (January 2008 to December 2018) were considered for the analysis. Concerning tinea capitis, 860 culture‐confirmed diagnoses were made during this 11‐year period, of which only 15 (1.5%) occurred in adults (15 patients). A disproportionately high number of patients were female and immunocompromised. Microsporum audouinii (20%) and Trichophyton rubrum (20%) were the most common isolates. Half of the cases were initially misdiagnosed. Regarding tinea barbae, 7 cases were diagnosed over this time period. Overuse of topical steroids was widespread in this population. Trichophyton rubrum was the infectious agent in all cases. Initial misdiagnosis was very common (43%). Adult tinea capitis and tinea barbae can still be observed in contemporary practice and remain a public health concern, with the immunosuppressed patient being particularly affected. Initial misdiagnosis is a common occurrence. Anthropophilic fungi are now the most common aetiologic agents of these infections, and they will probably continue to do so as the large urban centres expand peripherally. Awareness for this diagnosis is necessary to prevent unwarranted morbidity and costs.